2013
DOI: 10.1177/0021998313493808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxyapatite/collagen composite on osteogenic differentiation of rat bone marrow derived mesenchymal stem cells

Abstract: Combination of cells and materials opens a new option for tissue repair and regeneration. The aim of this study is to investigate the effects of hydroxyapatite/collagen composite on the osteogenic differentiation of rat bone marrow derived mesenchymal stem cells. The hydroxyapatite/collagen composites are synthesized by bioinspired mineralization and characterized by Fourier transform infrared spectrometry, X-ray diffraction, scanning electron microscope, thermogravimetric analysis and laser particle size anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The effects of HA/Col composite on the osteogenic differentiation of rBMSCs have been investigated in our previous study, and the results exhibit that the optimal concentration of HA/Col is 75 g/mL [20]. The cells of mechanical strain group in this study are subjected to a cyclic uniaxial stretch (0.5 Hz, 5% elongation).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The effects of HA/Col composite on the osteogenic differentiation of rBMSCs have been investigated in our previous study, and the results exhibit that the optimal concentration of HA/Col is 75 g/mL [20]. The cells of mechanical strain group in this study are subjected to a cyclic uniaxial stretch (0.5 Hz, 5% elongation).…”
Section: Discussionmentioning
confidence: 91%
“…Gene Forward primer Reverse primer ALP 5 -CATGTTCCTGGGAGATGGTA-3 5 -GTGTTGTACGTCTTGGAGAGA-3 cbfa1 5 -GCCGGGAATGATGAGAACTA-3 5 -GGACCGTCCACTGTCACTTT-3 COL1A1 5 -TTACTACCGGGCCGATGA-3 5 -CTGCGGATGTTCTCAATCTG-3 GAPDH 5 -TGTTCCTACCCCCAATGTATCCG-3 5 -TGCTTCACCACCTTCTTGATGTCAT-3 an important influence on the adaptation, remodeling, or reconstruction of tissues and cells [14][15][16][17]. Our group and other researchers have showed that hydroxyapatite/collagen (HA/Col) composite could induce the osteogenic differentiation of rat bone marrow derived MSCs (rBMSCs) [18][19][20]. These studies suggest an interesting biomaterial approach to affect the osteogenic differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The apatite is the inorganic phase in the bone matrix, configuring and providing natural bone with its mechanical properties. This bone apatite is predominantly composed of HA, (Huang et al, ; Zhou et al, ) yet its raw material comes from amorphous calcium phosphate (ACP) (Boonrungsiman et al, ; Liu et al, ), considered a more stable precursor of carbonated HA, which is the main mineral phase of mineralized tissues, found in the sites during initial mineral deposition of bone and dental tissues (Beniash, Metzler, Lam, & Gilbert, ; Mahamid, Sharir, Addadi, & Weiner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments for tissue and bone defects incorporating tissue engineering methods, such as the use of bone graft and stem cells, have been developed as an alternative to conventional defect treatments. 4 In recent decades, treatments involving the use of grafts have represented a novel approach to tissue and bone repair. Tissue engineering methods primarily intended for hard tissue repair not only rely on natural osteointegrative processes, but also on a material promoting osteointegration which is the bone graft.…”
Section: Introductionmentioning
confidence: 99%